Establishment of an Ex Vivo Tissue Culture Model for Evaluation of Antitumor Efficacy in Clear Cell Renal Cell Carcinoma - Hong, Shanjuan; Yuan, Qing; Xia, Haizhui; Dou, Yuan; Sun, Tiantian; Xie, Tian; Zhang, Zhiyin; He, Wei; Dong, Chen; Lu, Jian; Guo, Li; Ni, Ling (Frontiers in Oncology, 2022)
There are many potential immunotherapeutic targets for cancer immunotherapy, which should be assessed for efficacy before they enter clinical trials. Here we established an ex vivo cultured patient-derived tumor tissue model to evaluate antitumor effectiveness of one VISTA inhibitor, given that our previous study showed that VISTA was selectively highly expressed in human clear cell renal cell carcinoma (ccRCC) tumors. We observed that all the tested patients responded to the anti-VISTA monoclonal antibody as manifested by TNF-α production, but only a small fraction were responders to the anti-PD-1 antibody. Co-blockade of VISTA and PD-1 resulted in a synergistic effect in 20% of RCC patients. Taken together, these findings indicate that this ex vivo tumor slice culture model represents a viable tool to evaluate antitumor efficacies for the inhibitors of immune checkpoints and further supports that VISTA could serve as a promising target for immunotherapy in ccRCC.